THE URGENCY OF HALAL INDUSTRY DEVELOPMENT IN DRIVING NATIONAL ECONOMIC GROWTH - Muhammad Syarofi; M. Fikri Syaifulloh (JSE: Jurnal Sharia Economica, 2025)
The urgency of developing the halal industry lies in its role as a driving force for inclusive, sustainable, and globally competitive national economic growth. The halal industry is not merely a symbol of religiosity but also serves as a strategic instrument to enhance national productivity, expand export markets, create employment opportunities, and strengthen macroeconomic stability. This study aims to analyze the key strategies determining the success of halal industry development in Indonesia and its contribution to national economic growth. A qualitative approach was employed using the literature review method, drawing data from the Master Plan for Indonesia’s Halal Industry 2023–2029 and the KNEKS Report (2025). The findings reveal that the development of the halal industry is supported by four main pillars: improving productivity and competitiveness, strengthening policies and regulations, enhancing halal finance and infrastructure, and reinforcing halal branding and awareness. The contribution of this research lies in formulating a strategic framework that emphasizes the importance of multi-stakeholder collaboration to accelerate the transformation toward a halal-based economy. In conclusion, the development of the halal industry is not only a moral and spiritual obligation but also a visionary national economic strategy to achieve sustainable economic growth.